2017
DOI: 10.12710/cardiometry.2017.11.3545
|View full text |Cite
|
Sign up to set email alerts
|

The pattern of the immune processes during activation therapy with the use of microwave electromagnetic radiation

Abstract: The mechanisms of anti-tumor action of low intensity factors of activation therapy remain little investigated. The aim of the present paper is to study the changes in the immune system organs, the state of blood leukocytes and tumor area under effective activation therapy in tumor-bearing animals using EMR microwave range. The research is relevant due to the immune processes influence on cardiovascular system performance. Materials and methodsIn experiments on 77 albino outbred male rats with inoculated sarcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
1
0
0
2
Order By: Relevance
“…It has been resulted in an enhanced informative value of the signal and an increased biotropicity with respect to cancerogenesis inhibition. The produced effects have demonstrated that there is availability of ULF EMF and other factors of the wave nature to the key mechanisms responsible for the tumor growth that has been confirmed by our studies on some free-radical, immune and morphological processes [13,14,[16][17][18][19][20]. We have succeeded in the studies on the most important mechanism of an influence made by some rhythmic broad-band stochastic electromagnetic field patterns on intracellular potentials of a neuron and functional activity of cardiomyocytes [15].…”
Section: Activation Magnetotherapy (Emf Therapy)supporting
confidence: 69%
“…It has been resulted in an enhanced informative value of the signal and an increased biotropicity with respect to cancerogenesis inhibition. The produced effects have demonstrated that there is availability of ULF EMF and other factors of the wave nature to the key mechanisms responsible for the tumor growth that has been confirmed by our studies on some free-radical, immune and morphological processes [13,14,[16][17][18][19][20]. We have succeeded in the studies on the most important mechanism of an influence made by some rhythmic broad-band stochastic electromagnetic field patterns on intracellular potentials of a neuron and functional activity of cardiomyocytes [15].…”
Section: Activation Magnetotherapy (Emf Therapy)supporting
confidence: 69%
“…В этих случаях доля жизнеспособных клеток опухоли могла снижаться до 1/8 части поля зрения (при увеличении 10х40) (p<0,01 Неизбежно возникает вопрос о механизмах противоопухолевого влияния комбинированного воздействия. Как правило, при использовании неспецифических факторов, не оказывающих прямого повреждающего влияния на опухоль, речь может идти об активизации иммунных процессов, приводящих к сдерживанию опухолевого роста или даже к элиминации опухолевой ткани [19]. В случае торможения роста саркомы 45 под влиянием комбинированного воздействия была отмечена такая особенность микроструктурных изменений в ткани опухоли, как её выраженная инфильтрация плазмоцитами (рис.…”
Section: результаты исследования и их обсуждениеunclassified
“…В отличие от результатов, полученных на некоторых других экспериментальных моделях [4,8,19], у старых белых беспородных крыс-самцов с саркомой 45 под влиянием низкоинтенсивного модулированного ЭМИ КВЧ, предъявляемого в режиме активационной терапии, был отмечен только временный эффект -нестойкое торможение роста опухоли через две недели после начала воздействия. Антистрессорные изменения, вызванные ЭМИ КВЧ, оказались недостаточными для активизации эффективных противоопухолевых механизмов и достижения стойкого ингибирования роста опухоли.…”
Section: заключениеunclassified